SISTEM INFORMASI PENERIMAAN KAS DENDA KETERLAMBATAN ANGGOTA KSPPS BMT NUS KC. CILEUNYI - Maida, Rina Nur; Muthmainnah; Kurniawati, Rina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This study focuses on KSPPS BMT NUS Kc. Cileunyi, a cooperative operating in the field of savings, lending and financing based on Sharia principles. Currently, the accounting for late payment fines of members of this cooperative is still done manually. To increase the efficiency and accuracy of recording this information, we designed an overdue fine collection information system based on Microsoft Visual Studio 2010 and Microsoft Access 2007 as the database system. This research method includes interviews, observations, and document reviews. We applied a waterfall development approach when designing this system. Search results at KSPPS BMT NU Sejahtera Kc. Cileunyi emphasized that the process of recording monies collected from overdue fines still relies on a manual system. Therefore, we designed a new system based on Microsoft Visual Studio 2010 and Microsoft Access 2007 as the database. This system will help managers easily record the late payment fines of cooperative members. In addition, the system is expected to generate more accurate and efficient cash reports of late payment fines that can be presented to regulators for further assessment. By implementing this system, it is hoped that KSPPS BMT NUS Kc. Cileunyi can improve his financial management in a more professional manner.